End-to-end automated microfluidic platform for synthetic biology: from design to functional analysis. Issue 1 (December 2016) - Linshiz, Gregory; Jensen, Erik; Stawski, Nina; Bi, Changhao; Elsbree, Nick; Jiao, Hong; Kim, Jungkyu; Mathies, Richard; Keasling, Jay; Hillson, Nathan
Abstract Background Synthetic biology aims to engineer biological systems for desired behaviors. The construction of these systems can be complex, often requiring genetic reprogramming, extensive de novo DNA synthesis, and functional screening. Results Herein, we present a programmable, multipurpose microfluidic platform and associated software and apply the platform to major steps of the synthetic biology research cycle: design, construction, testing, and analysis. We show the platform's capabilities for multiple automated DNA assembly methods, including a new method for Isothermal Hierarchical DNA Construction, and forEscherichia coli andSaccharomyces cerevisiae transformation. The platform enables the automated control of cellular growth, gene expression induction, and proteogenic and metabolic output analysis. Conclusions Taken together, we demonstrate the microfluidic platform's potential to provide end-to-end solutions for synthetic biology research, from design to functional analysis.